Soil nutritional survey for soybean production in Uruguay - Bordoli, J. M.; Barbazán, M. M.; Rocha, L. (Agrociencia Uruguay, 2012)
The recent changes in the agriculture in Uruguay, by the adoption of no-tillage planting systems, have included the use of marginal soils for crop production, being the soybean the main crop that allowed those changes. Several questions have arisen about the sustainability of the intensive soil use of these new production systems. The objective of this work was to detect situations with greater probability of nutrient defi ciencies, using soybean as indicator crop. During crop seasons 2009/10 and 2010/11 a nutritional soil survey of soybean crops was conducted, collecting soil and leaf samples of 178 commercial fi elds widely distributed around the country, at the R1-R2 soybean growth stage. In half of the sites soybean was the main crop, and in the other half soybean was planted following winter crops. Soybean yield ranged from 511 to 5435 kg ha-1. In 34% of the fi elds pH was below 5.3, even in the traditional agricultural zone. In 54% of fi elds available P was below 12 mg kg-1 of P Bray-1, and 23% of the cases were below 0.30 cmolc kg-1 of exchangeable K. The concentrations of macronutrients in leaves for all the samples were: 3.88 (±0.66) % N; 0.26 (± 0.08) % P; 2.03 (±0.53) % K; 1.14 (±0.23) % Ca; 0.36 (±0.10) % Mg; and 0.29 (±0.07) % S. The micronutrient concentration means were 9, 77, 61, and 30 mg kg-1 of Cu, Fe, Mn, and Zn, respectively. The more frequently defi cient nutrients were P, K, and N, with 42, 39, and 13% of the fi elds with concentrations in leaves below the critical concentrations. The results show that the actual soybean productivity could be partially affected by nutrient defi ciencies, suggesting that soil pH, and P or K corrections need to be considered in the nutritional management program for each crop production system.